Three Dimensional Fractional Mellin Transform, and its Applications - Panda, Srikumar; Sinha, Arvind Kumar; Kilicman , Adem (The Nepali Mathematical Sciences Report, 2025)
We introduce three dimensional fractional Mellin transform and establish analytic theorem, boundedness theorem, inversion theorem and uniqueness theorem for three dimensional fractional Mellin transform. We present propositions of 3-dimensional fractional Mellin transform. We give some applications of 3-dimensional fractional Mellin transform for solving PDE’s.